THE PROBLEM OF INTER-CIVILIZATIONAL CHALLENGES IN THE SOCIAL DOCTRINE OF THE CATHOLIC CHURCH - Matyukhina, Oleksandra (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. Globalization processes in the modern world are the reason for the expansion of inter-civilizational contacts, cooperation, and at the same time tension. This indicates the strengthening of the inter-civilizational challenge in the modern world and the urgent need to form a response. The aim and tasks of the article are to examine the approach of the Catholic Church to the problem of intercivilizational challenges. Research methods determined by the aim of the study include the use of sociocultural and cultural-historical approaches and the method of conceptual analysis. Research results. The main provisions of Catholic social doctrine in the context of globalization on the basis of the study of encyclicals, speeches, and works of John Paul II, and Benedict XVI are highlighted. The article draws attention to the consistency, interconnectedness of their concepts, the formation of a holistic approach to inter-civilizational problems, and globalization. Particular emphasis is placed on the anthropocentricity and ethics of the Catholic Church’s approach to solving problems caused by globalization. It is emphasized that humanistic values are the basis of the social teaching of the Catholic Church. The Catholic Church points to an opportunity for humanity to move to a new level of development, to find ways to solve pressing problems in the process of globalization. The leading role should be played by the dialogue, first of all intercultural, broadly, inter-civilizational. The constructive inter-civilizational dialogue based on faith and universal human values is, from the point of view of Catholic social teaching, an appropriate response to inter-civilizational challenges. The dialogue foresees the active interaction of national cultures while preserving their independence and uniqueness. The goal of dialogue, John Paul II and Benedict XVI emphasize, is the man; the joint peaceful activity of mankind to achieve real progress. Discussion. Peculiarities of the approach to the problems and challenges of globalization in social science are the subject of interest of scientists and philosophical analysis. Conclusion. The social teaching of the Catholic Church emphasized that one can talk about progress if it provides life, and rights, leads to increasing standards of man’s living and creates conditions for self-realization. This approach to solving inter-civilizational challenges is relevant to the modern world.